An equation with one constant, two coefficients, and three terms will have the following structure:
- One constant term (a standalone number).
- Two coefficient terms (terms with variables that have numerical coefficients).
- Three total terms.
Looking at the options provided:
- 3x−y=5y → This simplifies to 3x - 6y = 0, which would have only two terms in the form of a polynomial (3x and -6y).
- 3x−4y=5y → This can be rearranged to 3x - 9y = 0. This has three terms (3x, -9y, and 0 which can be considered the constant term implicitly).
- 3x−4y=5x → Rearranging gives -2x - 4y = 0, again having two variables.
- 3x−4=5y → This rearranges to 3x - 5y - 4 = 0 and has three terms (3x, -5y, and -4).
Both 3x−4y=5y and 3x−4=5y can be argued to have three terms when rewritten in standard form.
However, the option 3x−4=5y clearly presents just one constant term (-4), two coefficient terms (3x and 5y), and a total of three unique terms.
Thus, the answer is:
3x−4=5y.